Used Car Price Prediction - Cozco Mauri, Yoset (2023)
On several occasions when a second-hand car is sold, the exact price is not known due to various factors, with which it can be sold at less or more value than it is actually worth, you will lose both buyers and sellers who try to calculate the value by intuition or with his knowledge in cars, but this sometimes fails. Then, with the help of organizing the data in a database, and comparing them with the help of software, we were able to get a much more accurate price, taking into account different factors that could modify the price of the car, such as time of use and quality. of the different parts, among others, achieving a much more accurate price than just using intuition.